Work Satisfaction Level of Private School Teachers in Yogyakarta Indonesia - Enung Hasanah; Suyatno Suyatno; Tugino Tugino; Syahid Ali (Randwick International of Social Science Journal, 2020)
This article aims to explore the level of teacher job satisfaction based on external factors, namely organizational policy factors, availability of promotion opportunities, and direct supervisor supervision. Participants in this study were 216 Muhammadiyah high school teachers in the Special Region of Yogyakarta, Indonesia, consisting of 79 men and 137 women. They become participants in this research voluntarily and are determined randomly. The data collection method was carried out by the teachers filling out the survey instruments deliberately. The data that has collected, then we process it using descriptive quantitative data processing techniques using SPSS 25. The results show that 1). The level of teacher job satisfaction from the aspect of organizational policy has a dominant distribution in the very high category (79.6%), in the high category was 16.7%, in the medium category was 3.2%, while those in the low category were as much as 0.5% ; 2) The level of teacher job satisfaction regarding supervision was included in the very high category (89.8%), in the high category was 18.3%, in the medium category was 0.9%, and in the low category were as much as 0.9%; 3) The level of teacher satisfaction on aspects of promotion opportunity has a dominant distribution in the very high category (81%), in the high category was 11.1%, in the medium category was 7.4%, and in the low category were as much us 0.5%. These results indicate that the level of job satisfaction of teachers at SMA Muhammadiyah in Yogyakarta Indonesia is at a very high level of satisfaction. In the future, further research is needed regarding the level of teacher job satisfaction from various other factors, both internal and external, to obtain a more comprehensive picture.